Helicobacter pylori eradication improves motor fluctuations in advanced Parkinson's disease patients: A prospective cohort study (HP-PD trial). - Praween Lolekha; Thanakarn Sriphanom; Ratha-Korn Vilaichone (PLoS ONE)
Background Helicobacter pylori (HP) is a bacterium associated with many gastrointestinal (GI) diseases and has shown a high prevalence in Parkinson's disease (PD). As HP-associated GI dysfunction could affect L-dopa (levodopa) absorption, HP eradication might improve the clinical response and decrease motor fluctuations. Methods A prospective cohort study was conducted on the clinical symptoms of PD patients with motor fluctuations. The 13C-urea breath test was used to diagnose a current HP infection. All patients with HP infection received a 2-week regimen of triple therapy. The changes in the Unified Parkinson's Disease Rating Scale (UPDRS) motor score, L-dopa onset time, wearing-off symptoms, mean daily on-off time, GI symptom scores, and quality of life score were measured at baseline and at a 6-week follow-up. Results A total of 163 PD patients were assessed, of whom 40 were enrolled. Fifty-five percent of the enrolled patients (22/40) had a current HP infection, whereas HP eradication was identified in 17 of 22 (77.3%) patients who received eradication therapy. Patients with HP eradication showed a significant decrease in daily 'off' time (4.0 vs. 4.7 h, p = 0.040) and an increase in daily 'on' time (11.8 vs. 10.9 h, p = 0.009). Total wearing-off score (4.4 vs. 6.0, p = 0.001) and the GI symptom score (8.1 vs. 12.8, p = 0.007) were significantly improved. There was no significant improvement in L-dopa onset time, UPDRS motor score, or quality of life score. Conclusions HP eradication leads to significant clinical improvement in the symptoms of PD. Eradication of HP not only increases the total daily 'on' time but also decreases wearing-off symptoms and improves GI symptoms.